Design and implementation of low-cost vein-viewer detection using near infrared imaging - Abdulrafa Hussain Maray; Saba Qasim Hasan; Naqaa Luqman Mohammed (Institute of Advanced Engineering and Science, 2023)
There are some medicines and medical treatments that need to be injected into the human body through the blood vessels, and this requires placing the cannula in the patient’s body. The blood vessels in the human body differ from one person to another, and medical personnel face major problems in finding the blood vessels in most cases, because of The difference in skin color, where it is difficult to see the blood veins in the skin with black pigment, and it is difficult to find it in people with obesity because of the layers of fat, and in children and newborns because these veins are small. This study talks about finding a way to photograph these veins, see them by design and implementation low cost prototype used equipment that were recycled old device, such as a web camera, infrared lamps and overhead device, All of these devices are of low cost. Then process these images using binary image, histogram equalization, segmentation and threshold to detect these blood veins. The algorithms for edges images detecting are many and complex, this study used five methods to detect vein image, such as Sobel, Laplacian, Canny, Roberts, and Prewitt.